2022
DOI: 10.1177/26331055221087740
|View full text |Cite
|
Sign up to set email alerts
|

Protein Network Analysis Reveals a Functional Connectivity of Dysregulated Processes in ALS and SMA

Abstract: Spinal Muscular Atrophy (SMA) and Amyotrophic Lateral Sclerosis (ALS) are neurodegenerative diseases which are characterized by the loss of motoneurons within the central nervous system. SMA is a monogenic disease caused by reduced levels of the Survival of motoneuron protein, whereas ALS is a multi-genic disease with over 50 identified disease-causing genes and involvement of environmental risk factors. Although these diseases have different causes, they partially share identical phenotypes and pathomechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In a recent study in ALS, Castro-Gomez et al found elevated TNT levels in ALS patients without TNI elevation or clinical signs of cardiac involvement, and thus proposed an extracardiac origin of TNT with TNT serving as a biomarker for lower motor neuron affection [ 135 ]. Although SMA and ALS have fundamentally different pathogenesis, they do partially share identical phenotype and pathomechanisms [ 136 ]. Changes of troponin isoform expression in muscles of SMA patients are described [ 137 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…In a recent study in ALS, Castro-Gomez et al found elevated TNT levels in ALS patients without TNI elevation or clinical signs of cardiac involvement, and thus proposed an extracardiac origin of TNT with TNT serving as a biomarker for lower motor neuron affection [ 135 ]. Although SMA and ALS have fundamentally different pathogenesis, they do partially share identical phenotype and pathomechanisms [ 136 ]. Changes of troponin isoform expression in muscles of SMA patients are described [ 137 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Together, recent findings open a new chapter in understanding the roles that R-loop mediated DNA damage and impaired DNA repair play in the pathogenesis of neurological disorders. Several studies, including the effect of ALS causing mutations on alteration of SMN function, loss of SMN containing gems in ALS patient cells, and the disruption of common protein networks in SMA and ALS have pointed to overlaps in the patho-mechanisms associated with two genetic neuromuscular disorders, ALS and SMA (Veldink et al, 2005 ; Achsel et al, 2013 ; Cauchi, 2014 ; Sun et al, 2015 ; Kubinski and Claus, 2022 ). One of the common links between different neurodegenerative disorders highlighted here is the gradual accumulation of DNA damage leading to genomic instability as one of the hallmarks of neurodegeneration.…”
Section: Mechanism Of R-loop Resolutionmentioning
confidence: 99%
“…SG are observed in most tested organisms ranging from yeast to mammals, establishing their formation as an evolutionary conserved stress-induced eukaryotic response. In mammals, SG form in virtually any analysed type of cells including neurons (Aramburu-Nunez et al, 2022), muscle cells (Kubinski and Claus, 2022), and blood cells (Ghisolfi et al, 2012), or tissues such as brain (DeGracia and Hu, 2007;DeGracia et al, 2008;Degracia and Hu, 2013) and muscles (Kubinski and Claus, 2022), either promoting cell adaptation to stress required for maintaining the normal cell physiology, or contributing to the development of stress-associated diseases including neurodegenerative pathologies (Hu et al, 2022) and cancer (Aulas et al, 2020;Lee and Namkoong, 2022). Stress-inducing SG includes environmental stress such as radiation (Moeller et al, 2004;Moutaoufik et al, 2014), exposure to chemical drugs such as arsenite (Kedersha et al, 2005), pathological stress such as viral infection (Mazroui et al, 2006), or physiological stress due to oxygen- (Moeller et al, 2004;Fahling, 2009), amino acids (Damgaard and Lykke-Andersen, 2011)-, or glucosedeprivation (Buchan et al, 2011;Wang et al, 2022), and chemotherapeutic stress generated during therapy (Fournier et al, 2010;Adjibade et al, 2015;Szaflarski et al, 2016;Adjibade et al, 2020).…”
Section: Introductionmentioning
confidence: 99%